Analisis Stabilitas Struktur Beton Bertulang Bangunan Sekolah Berdasarkan Respon Spektrum Terhadap Gaya Gempa Berdasarkan SNI 1726:2019 - Muammar F. Fahreza; Sapta Sapta; Amelia Rajela (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Education is the fundamental foundation for developing high-quality human resources. Along with the rapid development of the modern era, improving the quality of education has become essential, both in terms of curriculum, teaching staff, and supporting facilities. One of the most important aspects is the availability of educational buildings that are safe, comfortable, and compliant with technical construction standards. This study discusses the design of a ten-story reinforced concrete building using a Special Moment Resisting Frame (SMRF) system. The design was carried out in accordance with SNI 2847:2019 on Structural Concrete Requirements for Buildings and SNI 1726:2019 on Earthquake Resistance Design for Buildings and Non-Buildings, considering that the construction site is located in an earthquake-prone area. The structural analysis was conducted using modern structural analysis software, which included evaluating internal forces, deflections, and beam–column interactions under seismic loads. The results show that the designed structure performs well and meets all safety and serviceability requirements. The shear capacity of beams and columns satisfies the provisions of SNI 2847:2019, ensuring that the structure demonstrates a high level of reliability in resisting seismic forces. Therefore, the findings of this study indicate that the implementation of SMRF in high-rise educational buildings can serve as a safe, efficient, and standard-compliant design solution.